A Case of Anti-Jo-1 Myositis with Unique Biopsy Findings - Beenish Zulfiqar; Pavel Aksionav; Mohamad Bittar; Cathy Chapman (Case Reports in Rheumatology)
Antisynthetase syndrome (ASS) or anti-Jo-1 antibody syndrome has a classic clinical presentation including arthritis, myositis, interstitial lung disease, mechanic hands, and/or Raynaud’s phenomenon. The biopsy findings are distinctive from polymyositis or dermatomyositis. We describe an interesting case of ASS where a patient presented with significant muscle weakness, proteinuria, and interstitial lung disease. She also had positive Ro-52 antibodies in addition to anti-Jo-1 antibodies. Her biopsy findings were consistent with inflammatory necrotizing myositis.